Ethnopharmacology, Phytochemistry, and Pharmacology of the Genus Glehnia: A Systematic Review. (14th December 2019) - Yang, Min; Li, Xue; Zhang, Lei; Wang, Congcong; Ji, Mingyue; Xu, Jianping; Zhang, Keyong; Liu, Jicheng; Zhang, Chunhong; Li, Minhui
Abstract : Glehnia littoralis Fr. Schmidt ex Miq, the sole species in the genus Glehnia (Apiaceae), has long been used in traditional Chinese medicine to treat fatigue, weakness, stomach-yin deficiency, lung heat, cough, dry throat, and thirst. Recently, G. littoralis has also been incorporated into a wide range of Chinese vegetarian cuisines. Based on the comprehensive information, advances in botany, known uses, phytochemistry, pharmacology, and toxicity of G. littoralis, we aim to highlight research gaps and challenges in studying G. littoralis as well as to explore its potential use in plant biotechnology. This may provide more efficient therapeutic agents and health products from G. littoralis . A literature search of SciFinder, ScienceDirect, Scopus, TPL, Google Scholar, Baidu Scholar, and Web of Science, books, PhD and MSc dissertations, and peer-reviewed papers on G. littoralis research was conducted and comprehensively analyzed. We confirmed that the ethnomedical uses of G. littoralis have been recorded in China, Japan, and Korea for thousands of years. A phytochemical investigation revealed that the primary active compounds were phenylpropanoids, coumarins, lignanoids, and flavonoids, organic acids and derivatives, terpenoids, polyacetylenes, steroids, nitrogen compounds, and others. Our analysis also confirmed that the extracts of G. littoralis possess immunoregulatory, antitumor, anti-inflammatory, hepatoprotective, antioxidant, neuroprotective, antibacterial, antifungal, and analgesic properties. Although further studies are required, there is strong evidence of the antitumor and immunoregulatory potential of G. littoralis . Also, more studies are needed to elucidate the mechanisms of action of its active compounds (e.g., falcarinol and panaxydiol) before any clinical studies can be carried out.